NiBr2 complexes with triphenylarsine oxide (Ph3AsO). Two new interesting structures - Oliva, G.; Castellano, E. E.; Zukerman-Schpector, J.; Massabni, A. C. [UNESP] (Elsevier, 1984)
The synthesis and crystal structure of two complexes resulting from interaction between NiBr2 and triphenylarsine oxide (Ph3AsO) is described. Green and orange complexes can be obtained from the blue, probably tetrahedral complex [NiBr2(Ph3AsO)2], depending on the solvents used for recrystallization. NiBr2·4[(C6H5)3AsO]·8H2O (green): M = 1650.2, P21/c, a = 13.731(2), b = 16.267(3), c = 17.647(2) Å, β = 112.04(1)°, V = 3651.4 Å3, Z = 2, Dx = 1.501 g cm-3, CuKα, λ = 1.54184 Å, μ = 38.67 cm-1, R = 0.039, 3741 unique reflections, 3203 with I > 3σ(I). NiBr2·4[(C6H5)3AsO]·3|2(C6H5CH3)·H2O (orange): M = 1663.7, P1, a = 12.647(8), b = 13.953(5), c = 22.853(6) Å, α = 90.91(3), β = 96.70(4), γ = 111.16(4)°, V = 3727.4 Å3, Z = 2, Dx = 1.482 g cm-3, MoKα, λ = 0.71073 Å, μ = 30.48 cm-1, R = 0.087, 8600 unique reflections, 4293 with I > 3σ(I). In the green complex the Ni(II) ion is sited on a center of symmetry and is octahedrally coordinated to six water molecules, hydrogen bonded to the Ph3AsO molecules and to the bromide anions forming a second coordination sphere in a nearly octahedral arrangement. In the orange complex the cation is pentacoordinated with the four oxygen atoms of the Ph3AsO ligands forming the basis of a tetragonal pyramid and with one Br- anion in the apical position. The absorption spectrum of the orange complex is compared with the spectra of other Ni(II) square pyramidal complexes described in the literature. © 1984.